2019
DOI: 10.1016/j.jrp.2019.103847
|View full text |Cite
|
Sign up to set email alerts
|

Goal orientation and performance adaptation: A meta-analysis

Abstract: AcknowledgementsThis research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors. Declarations of interest: noneI wish to thank Thomas Staufenbiel for valuable comments on the first draft of this paper and both Kim Mehlitz and Wiebke Schmidt for help with coding. Furthermore, I am grateful toThe relationship between goal orientation and performance adaptation across studies was assessed in the present article. The relevance of performance adaptation ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 71 publications
1
36
3
1
Order By: Relevance
“…job performance). Furthermore, none of the mean correlations from previous meta-analyses devoted to performance adaptation, where predictors like Big Five personality traits or goal orientation were used (Huang et al, 2014;Stasielowicz, 2019b;Woo et al, 2014), reached the level identified here for cognitive abilities. Moreover, the heterogeneity of the effect sizes identified in the present meta-analysis indicates that there are circumstances where the predictive validity of cognitive abilities is somewhat higher than the mean effect size.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…job performance). Furthermore, none of the mean correlations from previous meta-analyses devoted to performance adaptation, where predictors like Big Five personality traits or goal orientation were used (Huang et al, 2014;Stasielowicz, 2019b;Woo et al, 2014), reached the level identified here for cognitive abilities. Moreover, the heterogeneity of the effect sizes identified in the present meta-analysis indicates that there are circumstances where the predictive validity of cognitive abilities is somewhat higher than the mean effect size.…”
Section: Discussioncontrasting
confidence: 59%
“…One objective of the current meta-analysis was to examine whether cognitive ability could be a more useful predictor than Big Five personality traits (Huang et al, 2014;Woo et al, 2014) and goal orientation (Stasielowicz, 2019b) as these predictors have been examined metaanalytically in the past. Superficially, examining the role of cognitive ability may seem trivial, since it has been established as a good performance predictor across different situations (Judge et al, 2007;Lang et al, 2010;Schmidt & Hunter, 2004, 1998.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations